Development of Ratiometric Fluorescent Biosensors for the Determination of Creatine and Creatinine in Urine - Duong, Hong Dinh (Sensors (Basel), 2017)
In this study, the oxazine 170 perchlorate (O17)-ethylcellulose (EC) membrane was successfully exploited for the fabrication of creatine- and creatinine-sensing membranes. The sensing membrane exhibited a double layer of O17-EC membrane and a layer of enzyme(s) entrapped in the EC and polyurethane hydrogel (PU) matrix. The sensing principle of the membranes was based on the hydrolytic catalysis of urea, creatine, and creatinine by the enzymes. The reaction end product, ammonia, reacted with O17-EC membrane, resulting in the change in fluorescence intensities at two emission wavelengths (λ(em) = 565 and 625 nm). Data collected from the ratio of fluorescence intensities at λ(em) = 565 and 625 nm were proportional to the concentrations of creatine or creatinine. Creatine- and creatinine-sensing membranes were very sensitive to creatine and creatinine at the concentration range of 0.1–1.0 mM, with a limit of detection (LOD) of 0.015 and 0.0325 mM, respectively. Furthermore, these sensing membranes showed good features in terms of response time, reversibility, and long-term stability. The interference study demonstrated that some components such as amino acids and salts had some negative effects on the analytical performance of the membranes. Thus, the simple and sensitive ratiometric fluorescent sensors provide a simple and comprehensive method for the determination of creatine and creatinine concentrations in urine.